Numerical issues in modeling combustion instability by quasi-1D Euler equations. (December 2017) - Frezzotti, Maria Luisa; D'Alessandro, Simone; Favini, Bernardo; Nasuti, Francesco
The present work is devoted to investigation of numerical issues related to combustion instability simulation through a quasi-1D Eulerian solver. The main aspects addressed are the choice of a suitable multispecies model and heat release response function formulation. Experimental data and high fidelity simulation results, available in literature, are reproduced with acceptable approximation. Main features of the flow field at limit cycle are shown. Moreover, a parametric study has been performed on time-lag response function characteristic parameters, leading to important conclusions on the pertinence of each assumption in the frame of a nonlinear tool.